Edukasi Seputar Covid-19 dan Pola Hidup Normal Baru kepada Masyarakat Desa Manyili, Kecamatan Takkalalla, Kabupaten Wajo dan Masyarakat Pengguna Media Sosial - A. Fatwa Bani Ilham; Fuad Akbar (Universitas Hasanuddin, 2021)
Community Service Program (KKN) is an actualization of students in devoting themselves to society and in an effort to achieve the aspirated Tridharma of Higher Education. Manyili Village is one of the villages included in the administrative area of Wajo Regency. A small village with the main source of income in agriculture that has been touched by technology although it is still not as massive as in other villages. In this village there are still no positive cases of Covid-19, this can occur due to the lack of mobility of residents outside the village who enter the village or because of the community's obedience to health protocols. However, in fact, now we can easily find people who do not apply health protocols in public places. Therefore, it is important to educate people who are not aware or tired of implementing health protocols. The method used is by providing posters in several public places, making educational discussion videos, and making a map of the distribution of Covid-19 sufferers. The results achieved have reached quite a few people, although they are still not optimal. In the end, protecting yourself from Covid-19 is a matter of awareness, people should think about their own health or at least not harm others